Enhancement of Academic Performance through Developing Cross-Cultural Communicative Competence: A Case Study of Students Majoring in Economics - Nataliia Guskova; Elena Golubovskaya (National Research University Higher School of Economics, 2023)
Background. The article questions the possibility to increase the level of foreign language command through developing cross-cultural communicative competence (CCC) in students of non-linguistic universities. Despite extensive literature on intercultural communication, there are obviously gaps in investigating the way it can and should be built and the potential impact it may have towards students' academic performance in general.   Purpose. The paper aims to find out the possible correlation between the level of CCC formation and a command of a foreign language in general. To pursue the goal, an in-depth research into the CCC structure was carried out and the idea to simultaneously develop all its components was proposed. Method. The paper reports on the results of the mixed-method research aimed at gathering the data and evaluating them both qualitatively and quantitatively. Senior students of the Higher School of Economics, Moscow, Russia, were selected and divided into the control and experimental groups with the subsequent training on the pre-designed curricula, with a primary focus on developing all the components of the CCC in the latter. To assess their performance, the method of experimental verification, self- and peer evaluation, educational observation, questioning method were employed. In-depth data analysis and verification provided post-active phase of the experiment conducted. Results. The results of the carried-out experiments, first, proved the hypothetical assumptions on the efficiency of developing all the four CCC simultaneously and, second, showed that the targeted CCC development contributes to improving foreign language acquisition in general, which is supported by the increase in 5 out of 6 didactic units of the final testing where the experimental group participants surpassed the students in the control group.   Conclusion. The study provides evidence for the impact CCC development has on the linguistic communicative competence. The devised methodology can be borrowed and customized for teaching foreign languages to university students and, in particular for developing intrinsic motivation through CCC. Further, future research should address particular components of the CCC.